Performance Evaluation of STARPAM Polymer and Application in High Temperature and Salinity Reservoir - Chengli Zhang; Peng Wang; Guoliang Song (International Journal of Analytical Chemistry)
Based on the properties of high temperature and salinity reservoir, the water-soluble polymer with good heat resistance and salt tolerance can be obtained through copolymerization between 2-acrylamide-2-methyl sulfonate monomer (AMPSN) and acrylamide monomer (AM) in water. The star shaped stable complexes (STARPAM) with the star nucleus of β-CD are prepared by living radical polymerization, which can improve the viscosity and change the percolation characteristics of the polymer in porous media. In the article, the performance of the STARPAM (star-shaped polymer) with heat resistance and salt tolerance was evaluated by comparing the viscosification property, heat and salt resistance, calcium and magnesium tolerance, and long-term thermal stability of STARPAM (star-shaped polymer) with those of HPAM (partially hydrolyzed polyacrylamide) and MO-4000 (linear polymer). The results of physical simulation experiment showed that the viscosity of the STARPAM is 3.3 times that of MO-4000 and 4 times that of HPAM under the conditions of mineralization degree of 20000 mg/L, concentration of 1500 mg/L, and 75°C, which indicated that heat resistance and salt tolerance of the STARPAM are excellent. Oil displacement experiments showed that STARPAM can enhance oil recovery by 20.53% after water flooding, and the effect of oil displacement is excellent. At present, 19 wells were effective with a ratio of 95.2%. Compared with before treatment, the daily liquid production increased by 136 m3, daily oil production increased by 44.6 t, water cut decreased by 4.67 percentage points, and flow pressure decreased by 1.15 MPa.